The utilization of CAMEL framework in analyzing the financial soundness of commercial banks in Malaysia: Pre and in the time of Covid 19 - Nurhuda Nizar; Ahmad Danial Zainudin; Siti Zaitun Saddam; Muhammad Ridzuan Abdul Aziz (Information Management and Business Review, 2023)
The COVID-19 pandemic has impacted many aspects of the economy, including commercial banking. This research aims to analyze the health of Malaysia's commercial banks before and during the COVID-19 pandemic. To accomplish this, the authors employed the CAMEL framework, widely recognized as one of the best tools for evaluating a bank's health. The study aims to comprehend the pandemic's impact on the financial health of banks during the pandemic. Secondary data was gathered from the financial statements of eight local commercial banks from 2017 to 2021. Results from this study suggest that the performance of commercial banks in Malaysia was generally stable and well-capitalized, with low non-performing loans and strong profitability before and during COVID-19. This study offers a new understanding of the effect of the pandemic on banking operations in Malaysia, a country whose financial system depends mainly on banks.